Teaching English Pronunciation to EFL Students - Iwan Perdana; Lulu Dwi Meiliani; Angga Taufan Dayu (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
The purpose of this research is to find out teaching method used by teacher in teaching pronunciation and to discover the strength and weakness of the method used in teaching pronunciation to EFL students at SMP Negeri 1 Martapura Timur. The researcher used qualitative descriptive as research design. A teacher and several students were interviewed. It was found that the teacher used Audio-lingual Method to teach pronunciation. The repetition drill as the technique was chosen. Weakness of this repetition technique made students get bored easily. It is not necessary to have sophisticated equipment to teach pronunciation. Teacher as role model for students is also effective.